Pengaruh Likuiditas dan Struktur Aktiva terhadap Struktur Modal pada Perusahaan Otomotif dan Komponen yang terdaftar di Bursa Efek Indonesia - Annisa Rahim; Mariaty Ibrahim (Jurnal Ilmiah Manajemen, Ekonomi dan Akuntansi, 2026)
The purpose of this study is to examine how asset structure and liquidity affect a company’s capital structure. Automotive and component firms that are listed on the Indonesia Stock Exchange between 2020 and 2024 are among the study objectives. Purposive sampling was used to pick the sample, which produced 12 businesses that satisfied the requirements. This topic is relevant because the automotive and component industry is a capital-intensive sub-sector that requires financial stability and accuracy in funding decisions, especially during the research period, which was marked by fluctuating economic conditions. Liquidity is measured through CR, QR, and CaR, while asset structure is proxied by FAR, and DER is used as an indicator of capital structure. Five years’ worth of financial statement data were examined using multiple linear regression in this quantitative analysis. The analysis’s findings demonstrate that CR significantly and negatively affects capital structure, suggesting that businesses with greater liquidity often employ less debt as internal funding is available. An rise in current assets other than inventory has not significantly affected the usage of debt since QR has a positive but has not significantly. Additionally, CaR exhibits a little negative impact, suggesting that cash has little bearing on the funding system. Additionally, there is no discernible impact of the asset structure on the capital structure. However, it has been demonstrated that both asset structure and liquidity have a substantial impact at the same time; the model can account for between 73 and 76 percent of the variance in capital structure